Hardness Testing As A Method To Evaluate The Resistance Of Concrete To Ice Abrasion In Marine Hydraulic Structures - BEKKER ALEKSANDR; UVAROVA TATIANA; POMNIKOV EGOR; SKLYAROV ALEXEY; SLAVCHEVA GALINA (Zenodo, 2018)
The main factor affecting the reliability of marine ice-resistant platforms (MIRP) is the ice re-gime in the construction site and, as a result, the ice pressure and its impacts on the structure. One of such impacts in the water areas with the dynamic with a dynamic ice drift regime regime of ice cover is the ice abrasion. Wear of concrete caused by the drifting ice cover contributes to the loss of thickness of concrete elements of the structure in the zone of variable level, causes the danger of exposure of the reinforcement and its accelerated corrosion in the marine environment, and consequently, may reduce the strength char-acteristics of these structural elements. The task of increasing the resistance of concrete to the abrasive impacts of the ice cover is directly related to the studies of their wear resistance and the determination of the requirements for the composition and structure of concretes used in the Arctic seas. The article substantiates the possibility of using hardness to evaluate the resistance of concrete to ice abrasion as a method of obtaining an independent direct quantitative index of concrete resistance associ-ated with the processes of destruction of concrete during ice abrasion and independent of the ice impacts parameters.The drifting ice cover affects the concrete causing thinning of the concrete elements of the structure in the variable level zone, constitutes a danger that the reinforcing steel can be exposed, and un-dergoes an accelerated corrosion in the marine environment, which may result in diminished strength characteristics of these structural elements. The task to increase the resistance of concrete to the ice cover abrading is directly related to the studies on the durability of concrete and the definition of the require-ments for the composition and structure of concretes to be used the Arctic seas. The article substantiates the use of the hardness testing to evaluate the resistance of concrete to ice abrasion as a method aimed to obtain an independent direct quantitative resistance index correlated with the concrete destruction pro-cesses caused by ice abrasion being independent of the ice impact parameters. The article deals with the possibilities to use and adapt the existing hardness testing methods to concrete as a brittle heterogeneous material as well as the optimal method, procedure, and algorithm to estimate the hardness of concrete. It presents the results of the tests of specimens that prove the possibility to determine the integral hardness of concrete basing on the statistically reliable evaluation of the hardness of each of its structural elements. To forecast and regulate the resistance of concrete to ice abrasion, it is proposed to identify the relation-ship between the integral hardness index of the concrete surface and the determined value of the depth of ice abrasion taking into account the variations in speed, temperature, and ice pressure. That was performed during the period from 2007 to 2014 on a special unit purposed to study ice abrasion effects on various types of building materials.